Risk Culture As A Solution To Face Covid-19 Pandemic - Mohamad Soleh (Ilomata International Journal of Management, 2020)
This paper is aimed to provide the best advice related to the importance of risk culture in facing Covid- 19 pandemic. As we know, until now, July 2020, the number of victims who were infected by Covid- 19 is increasing every day. The latest information on July 20, 2020, In Indonesia, there were more tha n 88,000 people were positive covid-19 and more than 4000 people died. This number continues to increase every day. It even happened in one day, the number of positive victims increased to more than 1000 cases. This indirectly indicates a failure in managing risk and a lack of awareness of all parties toward the importance of risk culture. In this paper, we will learn how to develop and nurture risk culture in organization by integrating risk management, transformational leader, and change management. This paper was written based on the study literatures. The result of the paper explains that risk culture is one of the most importance things which should be done in facing this Covid-19 pandemic and facing others risk. It is also provided guidelines related to what should be done or not when facing risks. For organizations, the given advice is that all parties in that organization (risk management, transformational leader, and change management) must collaborate in developing and nurturing risk culture. Moreover, specially to face Covid-19 Pandemic, the given advice is that all of the parties (community, government, and medical personnel) must understand the importance of risk culture and cooperate to face the pandemic.